Inspiring Muslim employees: divine speech - Fontaine, Rodrigue Ancelot Harvey; Wan Nasir, Zaireena (Asian Scholars Network, 2020)
This study is related to Islamic management. The aim is to test Nouman Ali Khan’s methodology found on www.bayyinah.tv. Khan says Muslims should start by exploring the linguistic miracles of the Qur’an before exploring the rest of the Qur’an. To test this claim, different groups of undergraduate and postgraduate students from the International Islamic University Malaysia watched videos from the bayyinah’s Divine Speech module. The qualitative and quantitative data supported Khan’s claim. The conclusion is that business leaders interested in developing a corporate culture that reflect Islamic values should consider using this methodology.